2019
DOI: 10.1101/648709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pooled CRISPR screening in pancreatic cancer cells implicates co-repressor complexes as a cause of multiple drug resistance via regulation of epithelial-to-mesenchymal transition

Abstract: Chemoresistance is the norm in pancreatic ductal adenocarcinoma (PDAC) leading to an abysmal five-year survival rate of less than 10%. We performed genome-wide CRISPR activation (CRISPRa) and CRISPR knock out (CRISPRko) screens to identify mechanisms of resistance to four cytotoxic chemotherapies (gemcitabine, 5-fluorouracil, irinotecan, and oxaliplatin) used to treat PDAC patients in two PDAC cell lines. Mirroring patient treatment outcomes, we found that multi-drug resistance genes were more likely to be ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Increased expression of CD44 , a cell surface protein important for cell adhesion and migration, is associated with a more mesenchymal-like phenotype which is characteristic of EMT 19 . This is in agreement with our finding that CD44 transcript and protein are more abundant in cells with HDAC1 overexpression and our past work showing that HDAC1 OE leads to increased migration 9 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Increased expression of CD44 , a cell surface protein important for cell adhesion and migration, is associated with a more mesenchymal-like phenotype which is characteristic of EMT 19 . This is in agreement with our finding that CD44 transcript and protein are more abundant in cells with HDAC1 overexpression and our past work showing that HDAC1 OE leads to increased migration 9 .…”
Section: Discussionsupporting
confidence: 94%
“…HDAC1 expression has been previously linked to increased cellular resistance to cytotoxic chemotherapeutic drugs 9 . To further evaluate the effects of HDAC1 overexpression on chemotherapeutic resistance, we used CRISPRa 17 to generate a stable MIA PaCa-2 cell line (MP2_HDAC1_OE) expressing HDAC1 at ~3 times the levels of the levels of the control line (MP2_NTC) which expresses a non-targeting control guide ( Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CRISPR screening uncovered that ABI2 is a key determinant of multiple drug resistance in pancreatic cancer cells. 17 Kyoung Lim's research demonstrated that the Doxo-induced HCC cell senescence can be attenuated by TIS21 through inhibiting linear actin nucleation, which is regulated by Nox4-ROS-ABI2-DRF signal cascade. 18 These studies indicated that ABI2 might play a crucial role in drug resistance and relapse of tumour.…”
mentioning
confidence: 99%